"You know you can do this, right?": developing geospatial technological pedagogical content knowledge and enhancing teachers' cartographic practices with socio-environmental science investigations. Issue 4 (4th July 2018) - Hammond, Thomas C.; Bodzin, Alec; Anastasio, David; Holland, Breena; Popejoy, Kate; Sahagian, Dork; Rutzmoser, Scott; Carrigan, James; Farina, William
ABSTRACT: Many barriers exist to K–12 classroom teachers' adoption and implementation of geospatial technologies with their students. To address this circumstance, we have developed and implemented a geospatial curriculum approach to promote teachers' professional growth with curriculum-linked professional development (PD) to support the adoption of socio-environmental science investigations (SESI) in an urban school environment that includes reluctant learners. SESI focus on social issues related to environmental science. The pedagogy is inquiry-driven, with students engaged in map-based mobile data collection and subsequent analysis with Web-based dynamic mapping software to answer open-ended questions. Working with four science and social studies teachers, we designed and implemented a sequence of three locally oriented, geospatial inquiry projects that were implemented with 140 9th grade students. We investigated how the geospatial curriculum approach impacted the teachers' geospatial pedagogical content knowledge (PCK), their cartographic practices, and promoted geospatial thinking and analysis skills with their students. Findings revealed strong growth in teachers' geospatial PCK, increased map use by teachers, use of maps as media for inquiry and not didactic instruction, and modeling to guide students' geospatial analysis using GIS. Implications for PD to promote teachers' geospatial PCK and in-class cartographic practices are discussed.